Translation and preliminary validation of the Modified Mini Mental State [3MS] in a Greek sample - Lyrakos, Georgios N; Nikolaidou, Georgia; Alizioti, Apostolia; Matsota, Paraskevi (Health & Research Journal, 2022)
Background: The Modified Mini Mental State (3MS) is the extended version of the original Mini Mental State test with additional items improving the coverage of the remaining cognitive functions of the original version. Aim: The aim of this pilot study is to translate the Modified Mini Mental State test and assess its psychometric properties, in order to enable the use of 3MS test for Greek speakers. Method and Material: Independent sample t-test analysis was performed to test for differences between the study groups (N=105) and dependent sample (N=37), while pair sample t-test for pre-post differences in the treatment group for the 3MS. Results: Cronbach’s a was 0.867 showing very good internal consistency. Children in the cases group presented significantly lower scores after the tonsil operation as compared to controls revealing good discriminant validity of the measurement. Finally, test-retest scores were shown to be significantly correlated, revealing excellent test-retest reliability of the measurement. Conclusions: The reliability and validity of the 3MS test is established for the healthy children undergoing routine surgery population.